Monomethyl fumarate treatment impairs maturation of human myeloid dendritic cells and their ability to activate T cells. (January 2019) - Mazzola, Maria Antonietta; Raheja, Radhika; Regev, Keren; Beynon, Vanessa; von Glehn, Felipe; Paul, Anu; Pierre, Isabelle; Kivisakk, Pia; Weiner, Howard L; Gandhi, Roopali
Background: Dimethyl fumarate (DMF) and its active metabolite monomethyl fumarate (MMF) effectively lead to reduction in disease relapses and active magnetic resonance imaging (MRI) lesions. DMF and MMF are known to be effective in modulating T- and B-cell responses; however, their effect on the phenotype and function of human myeloid dendritic cells (mDCs) is not fully understood. Objective: To investigate the role of MMF on human mDCs maturation and function. Methods: mDCs from healthy controls were isolated and cultured in vitro with MMF. The effect of MMF on mDC gene expression was determined by polymerase chain reaction (PCR) array after in vitro MMF treatment. The ability of mDCs to activate T cells was assessed by in vitro co-culture system. mDCs from DMF-treated multiple sclerosis (MS) patients were analyzed by flow cytometry and PCR. Results: MMF treatment induced a less mature phenotype of mDCs with reduced expression of major histocompatibility complex class II (MHC-II), co-stimulatory molecules CD86, CD40, CD83, and expression of nuclear factor κB (NF-κB) subunits RELA and RELB. mDCs from DMF-treated MS patients also showed the same immature phenotype. T cells co-cultured with MMF-treated mDCs showed reduced proliferation with decreased production of interferon gamma (IFN-γ), interleukin-17 (IL-17), and granulocyte-macrophage colony-stimulating factor (GM-CSF) compared to untreated cells. Conclusion: We report that MMF can modulate immune response by affecting human mDC function.